Job Satisfaction Level of Academic Members in Vietnamese Higher Education - Duong, Minh-Quang (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: Job satisfaction is an elusive and complex concept that has been a subject of intense research since the emergence of organizational studies. In recent years, several studies have examined the job satisfaction of academic members in higher education, little is known about lecturersâ job satisfaction in the developing countries like Vietnam. The purpose of this study is to ascertain job satisfaction level of academic members in Vietnamese universities. The study used a questionnaire to survey with 200 academic members from five member colleges of Vietnam National University of Ho Chi Minh City was selected as a statistical sample. The findings of study showed that most academic members of Vietnamese universities were satisfied with their job. Male faculty members were more satisfied than their counterparts. Academic members were generally satisfied with teaching support equipment, working insurance, teacher promotion, gender equality, in-service teaching training, in-service research training, work autonomy, colleague academic interaction, colleague social relationship, teaching load, research pressure, development aim of school, leadership style, campus landscape, and administration efficiency. Recommendations on the studyâs finding to the university management and policy makers are discussed to enhance the faculty job satisfaction. KEY WORD: Job satisfaction, developing country, higher education, academic members, Vietnamese universities, and university management and policy makers.Â RESUME: âTingkat Kepuasan Kerja Anggota Civitas Akademika di Perguruan Tinggi Vietnamâ. Kepuasan kerja merupakan konsep yang kompleks dan sulit dipahami yang telah menjadi subjek penelitian intensif sejak munculnya studi organisasi. Dalam beberapa tahun terakhir, banyak studi telah meneliti kepuasan kerja civitas akademika di perguruan tinggi, sedikit yang diketahui tentang kepuasan kerja para dosen di negara-negara berkembang seperti Vietnam. Tujuan dari penelitian ini adalah untuk memastikan tingkat kepuasan kerja anggota civitas akademika di perguruan tinggi Vietnam. Penelitian ini menggunakan kuesioner untuk survei dengan 200 anggota akademik dari lima kolej, yang ada di lingkungan Universitas Nasional Vietnam Kota Ho Chi Minh, terpilih sebagai sampel statistik. Temuan penelitian menunjukkan bahwa sebagian besar anggota civitas akademika di universitas Vietnam puas dengan pekerjaan mereka. Para dosen laki-laki lebih puas daripada rekan-rekan mereka yang perempuan. Anggota civitas akademika pada umumnya puas dengan dukungan peralatan mengajar, asuransi kerja, promosi pendidik, kesetaraan gender, layanan pelatihan mengajar, layanan pelatihan penelitian, otonomi kerja, interaksi akademik kolega, relasi sosial kolega, beban mengajar, tuntutan penelitian, tujuan pengembangan sekolah, gaya kepemimpinan, lanskap kampus, dan efisiensi administrasi. Rekomendasi dari temuan penelitian ini kepada manajemen universitas dan pembuat kebijakan adalah agar dibahas untuk meningkatkan kepuasan kerja para dosen.KATA KUNCI: Kepuasan kerja, negara berkembang, perguruan tinggi, anggota civitas akademika, universitas Vietnam, serta manajemen universitas dan pembuat kebijakan.About the Author: Minh-Quang Duong is a Lecturer at the Faculty of Education, University of Social Sciences and Humanities VNU-HCMC (Vietnam National University of Ho Chi Minh City), 10-12 Dinh Tien Hoang Road, District 1, Ho Chi Minh City, Vietnam. Corresponding author is: mqduong.ussh@yahoo.comHow to cite this article? Duong, Minh-Quang. (2014). âJob Satisfaction Level of Academic Members in Vietnamese Higher Educationâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7, No.1 [Mei], pp.33-42. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of article: Accepted (March 13, 2014); Revised (April 19, 2014); and Published (May 20, 2014). Â Â